Innovative route for the preparation of high-performance polyolefin materials based on unique dendrimeric silica particles. Issue 31 (5th July 2021) - Cecílio, Duarte M.; Fernandes, Auguste; Lourenço, João Paulo; McKenna, Timothy F. L.; Ribeiro, M. Rosário
Abstract : An innovative methodology for the preparation of high-performance polyolefin-based materials combining a unique dendrimeric silica carrier, a straightforward in situ supporting procedure and  in situ  ethylene polymerization technique was developed. Abstract : In this study, an innovative methodology for the preparation of high-performance polyolefin-based materials combining a unique dendrimeric silica (DS) carrier, a straightforward in situ supporting procedure and in situ ethylene polymerization technique was developed. Despite being inspired in the in situ supporting concept, it goes far beyond this, since its application is made in a different perspective, which is the production of high-performance polyethylene nanocomposites by in situ polymerization, where DS nanoparticles are aimed not only to act as a MAO carrier for ethylene polymerization but, also as a filler. This route combines metallocene supporting and polymerization in a single stage and avoids time-consuming and costly immobilization steps, allowing for a much more simplified experimental set-up. The impact of the immobilization procedure both on the catalytic activity for ethylene polymerization and on the morphological and thermal features of the ensuing polymers was investigated. The in situ supporting procedure was shown to yield highly active catalysts, compared to a common approach involving a two-step immobilization procedure, and in the same order of magnitude of the reference molecular catalyst in homogeneous conditions. Moreover, the in situ supporting route makes unnecessary the addition of external methyaluminoxane (MAO) cocatalyst thus, enabling a strong reduction of the MAO amount and potentially resulting in significant process cost savings. This way, polyethylene based materials with tunable molar masses, and desirable morphology and crystalline features were prepared, proving the method's versatility and ability in tailoring polymer properties, by changing the experimental conditions, and highlighting the potential of this methodology for the generation of highly performant HDPE nanocomposite materials for several applications.